Frequent missense and insertion/deletion polymorphisms in the ovine Shadoo gene parallel species-specific variation in PrP. - Nathalie Daude; Serene Wohlgemuth; Ekaterina Rogaeva; A Hossein Farid; Mike Heaton; David Westaway (PLoS ONE, 2009)
BACKGROUND: The cellular prion protein PrP(C) is encoded by the Prnp gene. This protein is expressed in the central nervous system (CNS) and serves as a precursor to the misfolded PrP(Sc) isoform in prion diseases. The prototype prion disease is scrapie in sheep, and whereas Prnp exhibits common missense polymorphisms for V136A, R154H and Q171R in ovine populations, genetic variation in mouse Prnp is limited. Recently the CNS glycoprotein Shadoo (Sho) has been shown to resemble PrP(C) both in a central hydrophobic domain and in activity in a toxicity assay performed in cerebellar neurons. Sho protein levels are reduced in prion infections in rodents. Prompted by these properties of the Sho protein we investigated the extent of natural variation in SPRN. PRINCIPAL FINDINGS: Paralleling the case for ovine versus human and murine PRNP, we failed to detect significant coding polymorphisms that alter the mature Sho protein in a sample of neurologically normal humans, or in diverse strains of mice. However, ovine SPRN exhibited 4 missense mutations and expansion/contraction in a series of 5 tandem Ala/Gly-containing repeats R1-R5 encoding Sho's hydrophobic domain. A Val71Ala polymorphism and polymorphic expansion of wt 67(Ala)(3)Gly70 to 67(Ala)(5)Gly72 reached frequencies of 20%, with other alleles including Delta67-70 and a 67(Ala)(6)Gly73 expansion. Sheep V71, A71, Delta67-70 and 67(Ala)(6)Gly73 SPRN alleles encoded proteins with similar stability and posttranslational processing in transfected neuroblastoma cells. SIGNIFICANCE: Frequent coding polymorphisms are a hallmark of the sheep PRNP gene and our data indicate a similar situation applies to ovine SPRN. Whether a common selection pressure balances diversity at both loci remains to be established.